ANALISIS BASIS KOMODITAS KUNYIT DENGAN MENGUNAKAN TEKNIK LQ (LOCATION QUENTIENT) DI KABUPATEN SUKABUMI - Sandi Agustian; Reny Sukmawani; Ema Hilma Meilani (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2022)
This research on the analysis of the turmeric commodity base in Sukabumi Regency aims to determine the results of the base analysis using the LQ (Location Quentient) technique. The source data in this study is secondary data that has been obtained and then a comparison analysis of turmeric is carried out from year to year during the last five years in all sub-districts in Sukabumi Regency. The LQ analysis carried out in this study was based on data on the area of ​​​​the turmeric plant spread in the sub-districts of Sukabumi Regency. The LQ value obtained for the turmeric commodity in Sukabumi Regency in the last five years (2016-2020) has fluctuated every year. The results of the research conducted show that turmeric in Sukabumi Regency is a non-basic commodity, meaning that turmeric has not been able to become a leading commodity competitively and comparatively with an LQ result of 0.8 for the 2016-2020 period. The increase in the amount of production and harvested area of ​​turmeric in the Sukabumi Regency area was due to turmeric having a large market and promising prices, while the decline was due to the unstable and unpredictable climate and weather resulting in crop failure.